Microwave-Assisted One Pot Three-Component Synthesis of Novel Bioactive Thiazolyl-Pyridazinediones as Potential Antimicrobial Agents against Antibiotic-Resistant Bacteria - Abu-Melha, Saraa (Molecules, 2021)
Pyridazine and thiazole derivatives have various biological activities such as antimicrobial, analgesic, anticancer, anticonvulsant, antitubercular and other anticipated biological properties. Chitosan can be used as heterogeneous phase transfer basic biocatalyst in heterocyclic syntheses. Novel 1-thiazolyl-pyridazinedione derivatives were prepared via multicomponent synthesis under microwave irradiation as ecofriendly energy source and using the eco-friendly naturally occurring chitosan basic catalyst with high/efficient yields and short reaction time. All the prepared compounds were fully characterized by spectroscopic methods, and their in vitro biological activities were investigated. The obtained results were compared with those of standard antibacterial/antifungal agents. DFT calculations and molecular docking studies were used to investigate the electronic properties and molecular interactions with specific microbial receptors.